Absorbed radiation doses in the thyroid as estimated by UNSCEAR and subsequent risk of childhood thyroid cancer following the Great East Japan Earthquake. (6th February 2020) - Ohira, Tetsuya; Shimura, Hiroki; Hayashi, Fumikazu; Nagao, Masanori; Yasumura, Seiji; Takahashi, Hideto; Suzuki, Satoru; Matsuzuka, Takashi; Suzuki, Satoshi; Iwadate, Manabu; Ishikawa, Tetsuo; Sakai, Akira; et al.
Abstract: The identification of thyroid cancers among children after the Chernobyl nuclear power plant accident propelled concerns regarding long-term radiation effects on thyroid cancer in children affected by the Fukushima Daiichi nuclear power plant accident in Fukushima, Japan. Herein we consider the potential association between absorbed dose in the thyroid and the risk of developing thyroid cancer as detected by ultrasonography on 300 473 children and adolescents aged 0–18 years in Fukushima. The absorbed dose mentioned in the present study indicates the sum of that from external exposure and that from internally deposited radionuclides. We grouped participants according to estimated absorbed doses in each of 59 municipalities in Fukushima Prefecture, based on The United Nations Scientific Committee on the Effects of Atomic Radiation (UNSCEAR) 2013 report. The 59 municipalities were assigned to quartiles by dose. We limited our analyses to participants aged ≥6 years because only one case of thyroid cancer was observed in participants aged ≤5 years; 164 299 participants were included in the final analysis. Compared with the lowest dose quartile, the age- and sex-adjusted rate ratios (95% confidence intervals) for the low-middle, high-middle and highest quartiles were 2.00 (0.84–4.80), 1.34 (0.50–3.59) and 1.42 (0.55–3.67) for the 6–14-year-old groups and 1.99 (0.70–5.70), 0.54 (0.13–2.31) and 0.51 (0.12–2.15) for the >15-year-old group, respectively. No dose-dependent pattern emerged from the geographical distribution of absorbed doses by municipality, as estimated by UNSCEAR, and the detection of thyroid cancer among participants within 4–6 years after the accident. Ongoing surveillance might further clarify the effects of low-dose radiation exposure on thyroid cancer in Fukushima.